DH2-dependent trans-acting siRNAs regulate leaf and lemma development in rice - Tang, Jun; Li, Tianye; Gao, Yuanzhuo; Li, Xinghang; Huang, Ziheng; Zhuang, Hui; He, Guanghua; Luo, Hongfa; Li, Yunfeng (Frontiers in Plant Science, 2025)
In most crops, the development of lateral organs such as leaves and floral organs plays important roles in the architecture of plants and grains and then determines the yield. Establishment of polarity in these lateral organs is one of the most critical events for their morphogenesis. However, the molecular mechanisms regarding this in rice remain unclear. Here, we isolated two allelic mutants named degenerated hull 2-1 and degenerated hull 2-2 (dh2-1 and dh2-2) in rice, exhibiting abaxially rolled leaves and rod-shaped lemmas. DH2 encoded the relatively conservative ARGONAUT 7 (AGO7) protein in plants and expressed in the lateral organs including leaf and floral organs. In addition, the overexpression lines of DH2 showed adaxially rolled leaves. Next, it was proved that DH2 was involved in the synthesis of tasiR-ARFs, the expression level of which was decreased sharply in lateral organs of dh2 mutants. Then, it was found that the expression of OsARF2, OsARF3, OsARF14, and OsARF15, the potential targets of tasiR-ARFs, was increased in lateral organs of dh2 mutants. However, it was not expected that the results of in situ hybridization showed that the four ARF genes were not expressed in WT lemma, whereas they were all ectopically expressed in rod-shaped lemma in dh2 mutants. Meanwhile, tasiR-ARFs were expressed in the whole lemma but not in the abaxial side. This means that there was no opposite expression of tasiR-ARFs and ARFs in the adaxial–abaxial of lemma. Therefore, according to our data, we believe that the pathway of OsAGO7–tasiR-ARFs in rice was more likely involved in the development of the whole lemma, not only the abaxial side, by restricting the ectopic expression of OsARFs in the whole lemma, which was different from that in the lateral organs of Arabidopsis.